2017
DOI: 10.1123/jtpe.2016-0128
|View full text |Cite
|
Sign up to set email alerts
|

Research on Preservice Physical Education Teachers’ and Preservice Elementary Teachers’ Physical Education Identities: A Systematic Review

Abstract: The purposes of this project were to conduct an overall review of research on preservice physical education (PE) teacher (referred to preservice PE teachers as preservice specialist) and/or preservice elementary teacher (referred to preservice elementary teachers as preservice generalist) PE identities and to identify any new trends in research on the topic. Studies were selected for analysis through searches of databases in English without time limits. In total, 27 articles were identified including 14 data-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…A literature search using PubMed, Google Scholar, Web of Science, and EBSCOhost databases was conducted to identify pertinent articles using the following keywords: Validity, concurrent validity, reliability, validation, global physical activity questionnaire, and GPAQ. These databases have been deemed to have the widest coverage of research articles in education, psychology, sports, PA, health, and physical education published in English [3,23,24]. Only peer-reviewed journal articles were selected for review if they fulfilled the following criteria: Written in English, analyzed/discussed the reliability and/or validity of the GPAQ.…”
Section: Methodsmentioning
confidence: 99%
“…A literature search using PubMed, Google Scholar, Web of Science, and EBSCOhost databases was conducted to identify pertinent articles using the following keywords: Validity, concurrent validity, reliability, validation, global physical activity questionnaire, and GPAQ. These databases have been deemed to have the widest coverage of research articles in education, psychology, sports, PA, health, and physical education published in English [3,23,24]. Only peer-reviewed journal articles were selected for review if they fulfilled the following criteria: Written in English, analyzed/discussed the reliability and/or validity of the GPAQ.…”
Section: Methodsmentioning
confidence: 99%
“…A case study of an experienced male PE teacher in Scotland (Thorburn, 2014) concurred that professional identity was closely linked to pedagogical practice. Keating et al (2017) conclude that this research demonstrates the importance of professional teacher identities on practices, and more specifically the lack of sustained research, hinders the development of high-quality PE teachers.…”
Section: Teacher Professional Identity and Pementioning
confidence: 80%
“…Seminal research on the construction of the professional identities of PE teachers focussed on how they negotiated the public perceptions of their marginal role in the academic hierarchy of a school (Hendry, 1975). A recent systematic analysis on preservice PE teachers' identities (Keating et al, 2017) revealed that although the research is distributed across many countries, only a small number of researchers are involved with most research focussed on the impact of physical education teacher education (see e.g. Devís-Devís & Sparkes, 1999;Dowling, 2011;Wrench & Garrett, 2012).…”
Section: Teacher Professional Identity and Pementioning
confidence: 99%
“…Keywords included ''preservice teacher'' or ''teacher candidate'', ''beliefs'', and ''physical education''. We used major databases for educational research in U.S. and China, including EBSCOhost, China Academy Journals, and CNKI (Keating et al 2017). We also restricted the search to include publications written in English and Chinese between 2000 and 2016 to develop domains based on a variety of studies in relevant contexts.…”
Section: Methodsmentioning
confidence: 99%